2022
DOI: 10.1177/20592043221105270
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Audiation or Tonal Memory? Evaluation of the Discriminant Validity of Edwin E. Gordon's “Advanced Measures of Music Audiation”

Abstract: Edwin E. Gordon developed the Advanced Measures of Music Audiation (AMMA) test to quantify the extent of an adult's stabilized audiation as a fundamental indicator of musical ability. Although intended to measure audiation exclusively, AMMA is based on a test design similar to the tonal memory subtest of the much older Measures of Musical Talents (SMMT) test developed by Carl Seashore (1919). However, previous studies have shown mixed results regarding AMMA's construct validity. It therefore remains unclear wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Not many non-Chinese standardized measures have been translated into simplified Chinese so far. Our search found that the standardized test most often used in Chinese music education research is the Advanced Measures of Music Audiation (AMMA; Gordon, 1989), the foundations of which are currently under intensive discussion and review in Western music education (Hanson, 2019; Platz et al, 2022). While the AMMA and more recently developed tests such as the Musical Ear Test (Wallentin et al, 2010), Profile of Music Perception Skills (Law & Zentner, 2012), and the Swedish Music Discrimination Test (Ullén et al, 2014) focus on perception abilities, the Gold-MSI also includes a variety of musical behaviors that are of interest for music education and music psychology alike.…”
Section: Concepts and Interests In Chinese Research On Musicalitymentioning
confidence: 99%
“…Not many non-Chinese standardized measures have been translated into simplified Chinese so far. Our search found that the standardized test most often used in Chinese music education research is the Advanced Measures of Music Audiation (AMMA; Gordon, 1989), the foundations of which are currently under intensive discussion and review in Western music education (Hanson, 2019; Platz et al, 2022). While the AMMA and more recently developed tests such as the Musical Ear Test (Wallentin et al, 2010), Profile of Music Perception Skills (Law & Zentner, 2012), and the Swedish Music Discrimination Test (Ullén et al, 2014) focus on perception abilities, the Gold-MSI also includes a variety of musical behaviors that are of interest for music education and music psychology alike.…”
Section: Concepts and Interests In Chinese Research On Musicalitymentioning
confidence: 99%